2016
DOI: 10.1038/srep33336
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary movement affects simultaneous perception of auditory and tactile stimuli presented to a non-moving body part

Abstract: The simultaneous perception of multimodal sensory information has a crucial role for effective reactions to the external environment. Voluntary movements are known to occasionally affect simultaneous perception of auditory and tactile stimuli presented to the moving body part. However, little is known about spatial limits on the effect of voluntary movements on simultaneous perception, especially when tactile stimuli are presented to a non-moving body part. We examined the effect of voluntary movement on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They compared the effects of voluntary and involuntary movements on multisensory temporal sensitivity, but the findings are not consistent even among the studies from the same laboratory. Although no significant differences in JNDs for the temporal disparity of auditory-somatosensory events between the voluntary and involuntary movement conditions have been reported (Frissen et al, 2012; Hao et al, 2015), improvement (Nishi et al, 2014) and even deterioration (Hao et al, 2016) of the JNDs has also been observed in the voluntary movement condition compared to passive and involuntary ones. The reason for this inconsistency between the findings of the previous studies is unclear.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They compared the effects of voluntary and involuntary movements on multisensory temporal sensitivity, but the findings are not consistent even among the studies from the same laboratory. Although no significant differences in JNDs for the temporal disparity of auditory-somatosensory events between the voluntary and involuntary movement conditions have been reported (Frissen et al, 2012; Hao et al, 2015), improvement (Nishi et al, 2014) and even deterioration (Hao et al, 2016) of the JNDs has also been observed in the voluntary movement condition compared to passive and involuntary ones. The reason for this inconsistency between the findings of the previous studies is unclear.…”
Section: Introductionmentioning
confidence: 96%
“…More recent studies have tried to further assess the effects of voluntary movements on multisensory temporal perception by introducing an involuntary movement condition in which the participants’ arm or finger is moved passively by a device (Frissen et al, 2012; Nishi et al, 2014; Hao et al, 2015, 2016). They compared the effects of voluntary and involuntary movements on multisensory temporal sensitivity, but the findings are not consistent even among the studies from the same laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Accidents are associated not only with psychocognitive decline but also with impaired fine motor control. Fine motor control is a high-level cognitive function of humans, which belongs to the category of voluntary movement, and occurs throughout the whole process of human daily life and social activities, such as reading, writing, speech, working, and some sports (Stippich et al, 2007;Bracci et al, 2012;Hao et al, 2016). Because fine movement is very important in daily life, much research has been conducted in the field of cognitive neuroscience, applying anatomical, physiological, and molecular biological methods to study voluntary movement and the mechanisms that govern it.…”
Section: Introductionmentioning
confidence: 99%